Variation of the contact time of droplets bouncing on cylindrical ridges with ridge size. - Andrew, M; Liu, Y; Yeomans, J (American Chemical Society, 2017)
Reducing the contact time between bouncing droplets and an underlying solid surface is relevant to a broad range of industrial applications, such as anti-icing and self-cleaning. Previous work has found that placing cylindrical obstacles on the substrate leads to a reduction in contact time. For obstacles large compared to the drop, this is a result of hydrodynamic coupling between the azimuthal and axial spreading directions. For obstacles small compared to the drop, the reduction in contact time is interpreted as being due to fast retraction along the cylindrical ridge, followed by drop breakup. Here we use simulations to discuss in greater detail the effect of varying the obstacle size on the dynamics of the drop bouncing. We investigate the crossover between the two regimes and explain why the contact time is minimized when the radii of the drop and the cylindrical obstacle are comparable.